Ultra‐Small Plutonium Oxide Nanocrystals: An Innovative Material in Plutonium Science. Issue 33 (7th July 2014) - Hudry, Damien; Apostolidis, Christos; Walter, Olaf; Janßen, Arne; Manara, Dario; Griveau, Jean‐Christophe; Colineau, Eric; Vitova, Tonya; Prüßmann, Tim; Wang, Di; Kübel, Christian; Meyer, Daniel
Abstract Apart from its technological importance, plutonium (Pu) is also one of the most intriguing elements because of its non‐conventional physical properties and fascinating chemistry. Those fundamental aspects are particularly interesting when dealing with the challenging study of plutonium‐based nanomaterials. Here we show that ultra‐small (3.2±0.9 nm) and highly crystalline plutonium oxide (PuO2) nanocrystals (NCs) can be synthesized by the thermal decomposition of plutonyl nitrate ([PuO2(NO3)2]⋅3 H2O) in a highly coordinating organic medium. This is the first example reporting on the preparation of significant quantities (several tens of milligrams) of PuO2 NCs, in a controllable and reproducible manner. The structure and magnetic properties of PuO2 NCs have been characterized by a wide variety of techniques (powder X‐ray diffraction (PXRD), X‐ray absorption fine structure (XAFS), X‐ray absorption near edge structure (XANES), TEM, IR, Raman, UV/Vis spectroscopies, and superconducting quantum interference device (SQUID) magnetometry). The current PuO2 NCs constitute an innovative material for the study of challenging problems as diverse as the transport behavior of plutonium in the environment or size and shape effects on the physics of transuranium elements.